Gestión de Activos en los Edificios de Casas Fiscales Ministerio De Defensa Nacional - Peñuela Suán, Luz Dary (Universidad Antonio Nariño, 2022)
Asset management as a strategy that generates organizational value has had an evolutionary story that moved from the maintenance of physical assets, which implied repairs and isolated actions that dealt with the use of assets, to the integration of processes and techniques that allow, in a coordinated manner, to get the most out of the assets, contribute significantly to the fulfillment of the objectives of the different institutions and organizations (Amendola, 2016). In Colombia, there is currently a significant development in the area of construction with special emphasis on the construction and sale of apartments for Unlike a few decades ago, when the main interest of real estate users were the houses, as stated by the newspaper Portafolio (2019) also mentioning that it sets them apart studio and apartments with less than 3 rooms, are the most commercialized, thanks to the fact that They can be located in highly developed areas at costs that are not as high as in the case of Bogotá Calle 93, El Virrey and Calle 72. Said panorama is presented not only at the level of private construction, in the sector The public has also sought the construction and remodeling of buildings that allow a greater user coverage in less space, an example of this is what is exposed by the construction company RUBAU S.A. (2016) who were in charge of the construction of three towers 10 of apartments in Bogotá, with eleven floors with a basement, for a total of 170 apartments intended for the use of fiscal houses for the National Army. Additionally, in cities such as Neiva, investment was made in the restructuring of the tower of buildings called La Gaitana, which has 16 apartments (National Army, 2018) and In Boyacá, 36 improved apartments were delivered in 3 towers, as part of the commitment to the institution in the well-being of its members (Ministry of Defense, 2018). On the other hand, the buildings of Fiscal Houses of the National Army sectional Brigade 13, as a population objective, they need to delve into the methodology of their maintenance at short, medium and long term, this is evidenced in the indicators offered by the Institute De Casas Fiscales Del Ejército (2022) in its management report valid for 2021, in it show the following figure.